Assessment of juvenile resistance of barley and wheat accessions to dark brown leaf spot - Neshumaeva Nadezhda A.; Sidorov Aleksandr V.; Gerasimov Sergei A. (E3S Web of Conferences, 2023)
Dark brown leaf spot of cereal crops caused by the Bipolaris sorokiniana fungus causes significant crop losses worldwide. To create new resistant varieties, it is necessary to use sources with a high level of resistance. In the laboratory of physiology and biotechnology of the Krasnoyarsk Research Institute of Agriculture, the juvenile resistance of the breeding material of spring barley and spring soft wheat of competitive variety testing to dark brown spot was evaluated. The most toxigenic isolates of Bipolaris sorokiniana were preliminarily selected for the production of inoculum, which was used to treat horizontally placed seedlings of the studied cereal samples in the 1-2 leaf phase. The development of the disease was assessed on a scale from 0 to 6. The sources of resistance included highly resistant samples, the damage of which did not exceed 2 points. These are samples of spring barley V19-6718, V21-6723, B25-6260, B33-6315, V33-6767, V34-6713, V40-6828, K-91-2, K104-1, S-106, K-134- 3 and spring soft wheat Altaiskaya 75, K-613-2, K-654-1, K-229-9, K-693-2, K-780-1, K-696-7, KSI-10, of interest for selection for fungal diseases.